2022
DOI: 10.1186/s13287-022-03074-w
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1T1 function in cell fate

Abstract: RUNX1T1 (Runt-related transcription factor 1, translocated to 1), a myeloid translocation gene (MTG) family member, is usually investigated as part of the fusion protein RUNX1-RUNX1T1 for its role in acute myeloid leukemia. In the main, by recruiting histone deacetylases, RUNX1T1 negatively influences transcription, enabling it to regulate the proliferation and differentiation of hematopoietic progenitors. Moreover, the formation of blood vessels, neuronal differentiation, microglial activation following injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…6D). While ChIP-seq binding data does not indicate whether these interactions are activatory or repressive, BCOR (binds 98.6% of cluster 2 genes) and RUNX1T1 (binds 95.1% of cluster 2 genes) are both known repressors 7375 . NEUROD1 (binds 94.6% of cluster 2 genes) however, is more complicated since it has been shown to act as an activator as well as repressor 76 , but it is possible that the I1-FFL motif is formed by the combined interactions of the target genes.…”
Section: Resultsmentioning
confidence: 97%
“…6D). While ChIP-seq binding data does not indicate whether these interactions are activatory or repressive, BCOR (binds 98.6% of cluster 2 genes) and RUNX1T1 (binds 95.1% of cluster 2 genes) are both known repressors 7375 . NEUROD1 (binds 94.6% of cluster 2 genes) however, is more complicated since it has been shown to act as an activator as well as repressor 76 , but it is possible that the I1-FFL motif is formed by the combined interactions of the target genes.…”
Section: Resultsmentioning
confidence: 97%
“…Skeletal muscle development, as known as myogenesis, is a complex multistep process and its underling molecular mechanism are not yet fully understood. RUNX1T1 has been shown to play an important role in cellular development, including cell proliferation and differentiation 33,34 . However, its role in regulating myogenesis and the underlying mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…RUNX1T1 has been shown to play an important role in cellular development, including cell proliferation and differentiation. 33,34 However, its role in regulating myogenesis and the underlying mechanisms remain unclear. In this study, we observed that goat RUX1T1 CDS sequence is highly homologous to that of ovine and both can encode 602 amino acids, 24 which is different from that of cattle and mice.…”
Section: Discussionmentioning
confidence: 99%
“…The last evidence showed that the adipogenesis induced by ZFP217 knockdown was caused by CCND1, which was mediated by METTL3 and YTHDF2 in an m 6 A-dependent manner [ 115 ]. Runt-related transcription factor 1 translocation partner 1 (RUNX1T1) is another novel adipogenic regulatory factor [ 116 ]. By modulating the amounts of m 6 A around splice sites, FTO regulates the exonic splicing of RUNX1T1, controlling RUNX1T1-S isoform expression and therefore modulating adipogenesis [ 117 ].…”
Section: A Modification and Adipogenesis Of Bmscsmentioning
confidence: 99%